2021
DOI: 10.1002/chem.202100113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Manganese Valence on Specific Capacitance in Supercapacitors of Manganese Oxide Microspheres

Abstract: Manganese oxides have attracted great interest in electrochemical energy storage due to high theoretical specific capacitance and abundant valence states. The multiple valence states in the redox reactions are beneficial for enhancing the electrochemical properties. Herein, three manganese microspheres were prepared by a one-pot hydrothermal method and subsequent calcination at different temperatures using carbon spheres as templates. The trivalent manganese of Mn 2 O 3 exhibited multiple redox transitions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The energy density ( E , W h kg –1 ) and power density ( P , W kg –1 ) of the as-assembled ASC device were calculated by the following equations: where C is the cell capacitance, V is the potential window, and Δ t refers to the discharging time.…”
Section: Simulation and Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy density ( E , W h kg –1 ) and power density ( P , W kg –1 ) of the as-assembled ASC device were calculated by the following equations: where C is the cell capacitance, V is the potential window, and Δ t refers to the discharging time.…”
Section: Simulation and Experimental Sectionmentioning
confidence: 99%
“…Transition metallic sulfides have attracted tremendous attention in the fields of ion batteries, supercapacitors, and electrocatalysis with the merits of natural abundance, controllable morphology, and high theoretical capacity. Binary metal sulfides are considered as potential battery-type materials owing to their multifarious metal species with rich valence states in Faradaic reactions. , The ideal electrode materials have high electrochemical activity and structural stability to cope with repeated cycles of electrochemical processes. The efficient processes require electrodes with high conductivity and abundant active sites. Previous reports have carried out exploratory work from the following two aspects: (1) from the perspective of morphology, the multi-dimensional structure can provide a wealth of available active sites to participate in surface reactions and achieve rapid reaction kinetics. , (2) In terms of composition, multiple components can build a relatively stable physical structure to resist the damage of the electrochemical cycle and ensure cycling stability. , The above two methods rely on external effects to improve performance. Heteroatom doping is expected to achieve simultaneous regulation of conductivity, activity, and stability from the intrinsic structure, such as sulfide-doped NiCoP and copper-doped NiCo 2 O 4 . , …”
Section: Introductionmentioning
confidence: 99%
“…Xu et al improved the pore structure of carbon AGLs with a specific capacitance of 186 F/g by introducing Mn ions [20]. Chen et al reported a superior capacitance of Mn 2 O 3 of 225 F/g in comparison with other manganese oxides, owing to the Mn 3+ /Mn 2+ and Mn 4+ /Mn 3+ transitions occurring during the redox reactions [21]. The self-assembly of mesoporous nanotubes assembled from interwoven ultrathin birnessite by Huang et al yielded a specific capacitance of 243 F/g [22].…”
Section: Introductionmentioning
confidence: 99%